In Vitro retinal ganglion cell differentiation and enrichment under the scope: do subtypes matter? - Baakdhah, Tahani W.; Sivak, Jeremy M. (Frontiers in Cell and Developmental Biology, 2026)
Retinal ganglion cells (RGCs) play a pivotal part transmitting visual data to the brain. Yet, damaged RGCs are unable to maintain and regrow axons and connectivity, as in the common blinding disease glaucoma. Thus, the idea of rescuing and replacing damaged RGCs holds immense therapeutic potential. In recent years pluripotent stem cells cultured in both 2D and 3D (retinal organoid) environments have generated RGCs from healthy- and patient-derived cells. These models can be used to study normal retinal physiology and compare it to the diseased retina. Although the effects of glaucomatous injuries on RGCs have been well-studied in animal models, much less is known about similar mechanisms in the human retina. Further, using in vitro-derived RGCs as a tool for cell characterization and replacement is still in its infancy. In particular, many distinct RGC subtypes have been described, and it remains unclear how well this diversity is reflected in the various differentiation protocols, or their functional roles in human health and disease. In this review we summarize the currently described subtypes of human RGCs and their markers and discuss recent evidence for subtype-specific vulnerabilities to injury and disease. Finally, we synthesize the limited evidence for subtype differentiation in human stem cell culture approaches. Increased understanding of this human RGC diversity will provide new tools to enrich for selective subtypes and ultimately fill key translational gaps in human glaucoma research.